Efficacy and safety of zolbetuximab for first-line treatment of advanced Claudin 18. 2-positive gastric or gastro-esophageal junction adenocarcinoma: a systematic review and meta-analysis of randomized controlled trials - Liang, Zhanpeng; Liu, Liwen; Li, Wenxia; Lai, Huiqin; Li, Luzhen; Wu, Jiaming; Zhang, Huatang; Fang, Cantu (Frontiers in Oncology, 2023)
Objective: Zolbetuximab is a "first-in-class" chimeric lgG1 monoclonal antibody targeting Claudin18.2 (CLDN 18.2). In recent years, several important trials have been published showing that zolbetuximab is associated with improved prognosis in patients with advanced gastric or gastro-oesophageal junction (G/GEJ) adenocarcinoma. This promises great change to the current treatment landscape.Therefore, we conducted a systematic review and meta-analysis to evaluate the efficacy and safety of zolbetuximab for first-line treatment of advanced CLDN 18.2 positive G/GEJ adenocarcinoma.: The following databases were searched for relevant studies: PubMed, EMBASE, and Cochrane library (updated June 10, 2023). All randomized trials comparing zolbetuximab plus chemotherapy versus first-line chemotherapy alone for first-line treatment of advanced CLDN 18.2 positive G/GEJ adenocarcinoma were eligible for inclusion. Data were analyzed using Review Manager 5.4.1 (Cochrane collaboration software). Primary outcomes and measures included overall survival (OS), progression-free survival (PFS), objective response rate (ORR) and adverse events (AEs).Results: This systematic review and meta-analysis included three randomized controlled studies involving 1402 patients (699 receiving zolbetuximab plus chemotherapy and 703 receiving chemotherapy alone). Compared with chemotherapy alone, zolbetuximab plus chemotherapy significantly improved OS (HR = 0.73; 95% CI: 0.68-0.84) and PFS (HR = 0.64; 95% CI: 0.50-0.82), but did not result in a higher ORR (RR = 0.92; 95% CI: 0.82-1.03). Further analysis of CLDN 18.2 expression show a more significant benefit for OS (HR = 0.69; 95% CI: 0.55-0.87; P = 0.002) and PFS (HR = 0.61; 95% CI: 0.44-0.84; P = 0.003) from zolbetuximab in patients with high expression, while there was significant benefit in patients with lower expression. In terms of AEs, zolbetuximab plus chemotherapy was associated with higher risk of grade 3 and higher AEs, but increased risk of nausea and vomiting were more common.This systematic review and meta-analysis revealed that the effect of zolbetuximab plus chemotherapy was superior to that of chemotherapy alone for first-line treatment of advanced CLDN 18.2-positive G/GEJ adenocarcinoma. Thus, zolbetuximab plus chemotherapy represents a new first-line treatment for these patients. Zolbetuximab plus chemotherapy was associated with higher risk of grade 3 and higher AEs, but was generally manageable.Systematic review registration: https://www.crd.york.ac.uk/prospero, identifier (CRD42023437126).